ASSISTANCE AND UTILIZATION OF G-SUITE WITH QR-CODE IN IMPROVING ADMINISTRATIVE SERVICES FOR RT RESIDENTS. 002/027 AT TAMAN GRAHA ASRI HOUSING GRAHA MINIMALIST BLOCK SERANG CITY - Hafidz Hanafiah; Dede Gunadi (International Journal of Engagement and Empowerment, 2021)
The Neighborhood Association is part of the kelurahan or village, coordinating with the Rukun Warga. In the technical implementation, the RT serves as a bridge or liaison with other agencies or organizations that have legality from the kelurahan or village. Concerning the duties and functions of the RT, the administration is something that residents often do regarding the information on residents' domicile and other matters that are more related to administrative permits for residents and organizations within the RT area. Along with the development of the era of the use of all-digital technology. Citizen services can improve by implementing widely available applications in cyberspace. One of them is the use of Google Suite, which is usually used in online learning education, and the QR-Code system, which is widely used by private organizations, government organizations, and even other organizations. In implementing PKM this time, an analysis was carried out first regarding housing problems, incredibly complex houses. Counseling and introduction of applications, lastly, mentoring and implementation in the RT area. 002 Taman Graha Asri Housing Minimalist Graha Block in Serang City. The results can be a benefit for the RT management. 002 is that services can be carried out anywhere, anytime, without meeting in person because of each other's busyness. This system makes it easier for residents to receive increased administrative services for residents of RT.002